Allah Almighty said: “Allah will erase what He wills, and it will be established with Him the Mother of the Book”. A comparative exegesis study in the commentaries of the Sunnis - Roman, Toqa; Al-Zoiut, Abdallah (Jordan Journal of Islamic Studies, 2023)
This study deals with verse 39 of Surat Al-Raad, a comparative explanatory study in the interpretations of the Sunnis, as it stands on the sayings of the interpreters in the verse, with the evidence relied upon in these sayings, and examines the validity of these evidence, and the validity of its inference to the aforementioned saying, and then It examines the reason for the differing interpreters in the verse, leading to the most correct opinion among these multiple sayings, supported by evidence, which was reached through weighted rules considered by the scholars of interpretation and the sciences of the Qur’an from the applicants and the late, and this study came in a preliminary and two articles, each of which includes two requirements. Finally, it reached to many of results, the most important results are: the ability to combine many of the sayings in which the difference is thought, in addition to the incorrectness of many of the reliable evidence, as well as the error of inferring benefit of some correct evidence on some of the said statements.